Reversing delegation? Politicization, de‐delegation, and non‐majoritarian institutions. Issue 1 (17th October 2022) - Thatcher, Mark; Sweet, Alec Stone; Rangoni, Bernardo
Abstract: Elected governments and states have delegated extensive powers to non‐majoritarian institutions (NMIs) such as independent central banks and regulatory agencies, courts, and international trade and investment organizations, which have become central actors in governance. But, far from having resolved the balance between political control and governing competence or removed certain issues from political debate, NMIs have faced challenges to their legitimacy by elected officials and sometimes attempts to reverse delegation through "de‐delegation". Our special issue studies the politicization of NMIs, and then whether, why and how it leads to de‐delegation through reducing the formal powers of NMIs or increasing controls over them. In this article, we examine how to analyze de‐delegation, how politicization of NMIs has developed, and how it has affected de‐delegation. We underline not only institutional rules that constrain elected officials but also the actions of NMIs themselves and their relationships with other NMIs as part of multi‐level governance systems. We find that politicization has varied, but even when strong, elected officials have not introduced widespread and long‐lasting de‐delegation; on the contrary, they have frequently widened the powers of NMIs. Insofar as elected politicians have sought to curb NMIs, they have often preferred to use existing controls and non‐compliance. Finally, we consider the wider implications of the combination of politicization and lack of de‐delegation for broader issues of governance such as the division of powers between the elected and unelected and democratic accountability.